Working Mother Parenting Style and Adolescent Personality to The Learning Motivation of Midwifery Students - Winarsih Winarsih; Wiwin Hindriyawati; Era Revika (Jurnal SMART Kebidanan, 2022)
ABSTRACTThe role of the mother is to meet the physiological needs of the child patiently. patiently. and consistently. Mothers are also tasked with organizing. controlling. being role models. and providing economic support. Islam does not forbid a mother to work because the law is Sunnah. it is even worth giving alms. Adolescents who have a working mother are considered to have lost a mother figure who plays an important role in personality formation during their transition period. This study aims to determine the correlation between parenting and adolescent personality on the learning motivation of students of the DIII Midwifery Study Program STIKES AKBIDYO. Ani is a descriptive correlational survey research. The study used a total population sampling technique. This study involved 33 respondents. Data were collected using a questionnaire. Data were analyzed using SPSS with Kendall's tau to determine the correlation between the two variables. From the results of this study. it can be concluded that there is no correlation between parenting and adolescent personality on the learning motivation of midwifery diploma students of STIKES AKBIDYO. The data of this study indicate that democratic parenting produces students with good personalities and learning motivation. This means that democratic parenting can produce children who have good personalities and motivation to learn. Suggestion: For working mothers: Apply the right parenting pattern. especially during the golden age. For further research: Further research can be carried out on a larger sample and carried out qualitatively to obtain more in-depth data. Keywords: working mother; parenting style; personality; adolescents; motivation ABSTRAKPeran ibu dalam keluarga memenuhi kebutuhan fisiologis anak dengan sabar. telaten. konsisten. mengatur. mengendalikan anak. sebagai contoh. teladan. manager dan menyediakan dukungan ekonomi. Islam tidak melarang seorang wanita terlebih ibu yang sudah memiliki anak untuk bekerja. hukum  sunnah bahkan bernilai sedekah. Bagi remaja yang memiliki seorang ibu yang bekerja memiliki proses pembentukan kepribadian yang menarik untuk diteliti. karena remaja telah kehilangan seorang figure ibu yang seharusnya memiliki peran utama dalam pembentukan kepribadian pada masa transisi ini. Tujuan peneliti ini dimaksudkan untuk mengetahui hubungan  parenting style ibu bekerja dan kepribadian remaja dengan motivasi belajar mahasiswa Prodi DIII Kebidanan STIKES AKBIDYO. Penelitian ini merupakan penelitian survei deskriptif korelasional. Teknik sampling total popilasi sejumlah 33 responden. alat ukur menggunakan questioner. Data dianalisis menngunakan SPSS dengan Kendall's tau melihat korelasi antar dua variable. Dari penelitian yang telah dilakukan dapat disimpulkan bahwa tidak ada hubungan antara parenting style ibu bekerja dan kepribadian remaja dengan Motivasi Belajar Mahasiswa Prodi DIII Kebidanan STIKES AKBIDYO. Tetapi melihat data yang ada dari Parenting style ibu bekerja adalah demokratis. kepribadian  mahasiswa adalah kepribadian cukup baik dan motivasi belajar mahasiswa adalah cukup baik maka dapat di jelaskan bahwa ibu bekerja yang memiliki gaya pola asuh demokratis mempu menghasilkan anak yang memiliki kepribadian baik dan sehingga memiliki  motivasi belajar yang tinggi. Saran : Bagi Ibu yang bekerja memberikan asuhan kepada anaknya terutama dimasa masa golden age anak perlu ditanamkan ketauhitan dan akhlak baik. Bagi penelitian selanjutnya Penelitian selanjutnya perlu diperluan besar sampel dan metode dipadukan dengan jenis penelitian kualitatif Kata kunci: ibu bekerja; pola asuh; kepribadian; remaja. motivasi